Managing maize under pest species competition: Is Bt (Bacillus thuringiensis) maize the solution?. Issue 6 (10th June 2016) - Catarino, Rui; Ceddia, Graziano; Areal, Francisco; Parisey, Nicolas; Park, Julian
Abstract: Transgenic crops that contain Cry genes from Bt (Bacillus thuringiensis) have been adopted by farmers over the last 17 yr. Unlike traditional broad‐spectrum chemical insecticides, Bt 's toxicity spectrum is relatively narrow and selective, which may indirectly benefit secondary insects that may become important pests. The economic damage caused by the rise of secondary pests could offset some or all of the benefits associated with the use of Bt varieties. We develop a bioeconomic model to analyze the interactions between primary and secondary insect populations and the impact of different management options on insecticide use and economic impact over time. Results indicate that some of the benefits associated with the adoption of genetically engineered insect resistant crops may be eroded when taking into account ecological dynamics. It is suggested that secondary pests could easily become key insect pests requiring additional measures, such as insecticide applications or stacked traits, to keep their populations under the economic threshold.